ANALYSIS OF THE INFLUENCE OF USING ACCESS POINTS IN STRENGTHENING THE NETWORK RECEIVING SIGNALS IN HOUSEHOLDS - Fauziah, Hanifah Nur; Marpaung, Jannus; Imansyah, Fitri (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
From the results of the RSSI values that occur when researchers observe the walktest method and observe network quality in bandwidth when not using additional devices in the form of access points and after adding bandwidth in the form of access point devices, which are used to test and analyze the quality of an ICONNET telecommunications service system that used. The data retrieved shows that the RSSI results show a good category and index after the addition of an access point device, which helps to strengthen a multilevel home network. In this case several factors affect a network quality. One of them is the number of users at that time, the number of partitions in the terraced house affects the quality of the network, as well as the existence of several room dividers that cannot access the wifi. However, we can handle some of these factors by adding an access point to the multi-storey house. Distance and cable length, that is, cable distance and length greatly affect a network quality, the farther we are from the wifi router, the worse the quality of the network we get, but after adding an access point. In table 4.3 is the result of RSSI recapitulation on 3 different bandwidths. different, the average results for each bandwidth are shown in the form of data before with a bandwidth of 10 Mbps with data before -64 dBm and data after or data after the addition of an access point with an RSSI value of -47 dBm, so there is an increase in the bandwidth of 10 Mbps, namely -17 %,